Current Perspectives on Awareness Information to Support Real-Time Communication - Tang, John; Chen, Henry; Chin, Angela; Hehmeyer, Alex; Suciu, John; Palmer, Jim; Shtiegman, Eran (Proceedings of the 2013 International Conference on Collaboration Technologies and Systems, 2013)
Sharing awareness information to help remote people establish real-time communication has been a research area for the past couple decades. Much of the work so far has focused on sharing awareness for communication availability in the work setting. Yet several recent trends suggest the need to reconsider the contexts and assumptions around awareness research. Increasing deployment of communication technology in homes and the blurring of home and work boundaries means that more communication interactions involve the home. The popularity of mobile smartphones adds the mobile context and the sensor capabilities integrated into mobile devices. Given the broadened scope of where and how communication occurs and the importance of being able to smoothly negotiate starting and ending conversations, there is an opportunity to reconsider awareness research in today’s environment. We identify current challenges and opportunities in awareness research from perspectives beyond focusing just on the workplace to include technologies and use practices in the home and mobile contexts.